Attitudes on regulatory framework of student employment study upon a student population in Croatia before new legislation - Mihelja Žaja, Maja; Jakšić, Saša, ekonomist; Špoljar, Karlo (2018)
Students enter the labour market through a Student Service to have the opportunity to pay for tuition fees or to earn additional income that would allow for the parents or guardian's budget to be disbursed. Although almost 70% of full-time students were working through a student contract in 2016, the Regulation on intermediaries for the employment of full-time students from 1996 was the only legal document that was regulating student employment. Due to improperness of this document and the fact that student employment is not under the Labour Law, in November 2017 the Croatian Government published a proposal for the new Student Employment Act, which was passed in November 2018. Subsequently, the reform of the regulatory framework of student employment is important to the student workforce. According to the Regulation in force, there is no constraint on the maximum weekly working hours or maximum annual earnings. Nevertheless, student income can become taxable under the rules of Personal Income Tax Law if it exceeds the annual limit of 60,600.00 HRK. Consequently, the reform of personal income tax is also significant for students if they do not want to become a taxpayer of personal income tax. Based on this, the main goal of this paper is to analyse attitudes of students towards the regulatory framework of student employment, reform of personal income tax and their work under the mediation of the Student Centre. In order to question student attitudes, the questionnaire was used and the results of the analysis carried out before changes in legislation, in February and March 2018, indicate that students were not satisfied with the existing regulatory framework and the personal income tax reform and that they expect the improvement of working conditions with the implementation of the new Student Employment Act.
Studenti se uključuju na tržište rada preko studentskog servisa kako bi imali priliku platiti školarinu ili zaraditi dodatne prihode s ciljem financijskog rasterećenja roditelja ili staratelja. Iako je gotovo 70% redovnih studenata radilo preko studentskog ugovora u 2016. godini, jedini pravni dokument koji je regulirao zapošljavanje studenata je bio Pravilnik o posredovanju pri zapošljavanju redovitih studenata iz 1996. godine. Zbog neprimjerenosti ovog dokumenta i činjenice da zapošljavanje studenata nije regulirano Zakonom o radu, u studenome 2017. godine Vlada Republike Hrvatske objavila je prijedlog novog Zakona o obavljanju studentskih poslova, koji je izglasan u studenom 2018. godine. Zbog toga, reforma regulatornog okvira zapošljavanja studenata važna je za studentsku radnu snagu. Prema važećem Pravilniku, ne postoji ograničenje maksimalnog tjednog radnog vremena ili maksimalne godišnje zarade. Unatoč tome, dohodak studenata može postati oporeziv prema pravilima Zakona o porezu na dohodak, ako premašuje godišnju granicu od 60.600,00 kuna. Slijedom toga, reforma poreza na dohodak je također značajna za studente ako ne žele postati poreznim obveznikom poreza na dohodak. Na temelju toga, glavni je cilj ovoga rada analizirati stavove studenata prema regulatornom okviru zapošljavanja studenata, reformi poreza na dohodak i njihov rad pod posredovanjem Studentskog centra. Kako bi se ispitali stavovi učenika, korišten je upitnik, a rezultati analize provedeni prije izmjene zakonodavnog okvira, u veljači i ožujku 2018. godine, pokazuju da studenti nisu zadovoljni postojećim regulatornim okvirom i reformom poreza na dohodak, te da očekuju poboljšanje radnih uvjeta stupanjem na snagu novog Zakona o obavljanju studentskih poslova.
Bibliografija: str. 37-38.
Abstract ; Sažetak.
Keywords: Studenti -- Prihodi -- Regulatorni okvir -- Porez na dohodak -- Studentski centar; Hrvatska